(untitled) (Literary Voice, 2023)
A Noble King of Bidanuru is an historical novel written by Basavaraj Naikar that explores the history and trajectory of the Keladi kingdom. Although the novel tells the stories of notable kings of the Keladi kingdom, it focuses more on Raja Sivappa Nayaka’s development from Raja Virabhadra Nayaka’s nephew to a powerful ruler of the Keladi kingdom.